2019
DOI: 10.7554/elife.47990
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated phosphatidylcholine turnover in macrophages promotes adipose tissue inflammation in obesity

Abstract: White adipose tissue (WAT) inflammation contributes to the development of insulin resistance in obesity. While the role of adipose tissue macrophage (ATM) pro-inflammatory signalling in the development of insulin resistance has been established, it is less clear how WAT inflammation is initiated. Here, we show that ATMs isolated from obese mice and humans exhibit markers of increased rate of de novo phosphatidylcholine (PC) biosynthesis. Macrophage-specific knockout of phosphocholine cytidylyltransferase A (CC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Recently, in Pcyt1a-deficient macrophages, a decreased rate of PC turnover facilitated a shift toward more polyunsaturated FAs in membrane phospholipids, which stemmed their inflammatory potential. (42) Although our study focused on the consequence of exogenous FA treatment on choline transport and subsequent metabolism, we learned that (1) PC metabolism can be regulated because of pathway interruptions and (2) it is possible that alterations in phospholipid FA composition might alter the membrane properties that can affect transport proteins. (43) Finally, many studies have now linked phospholipid biosynthetic pathways with diacylglycerol and triglyceride synthesis, storage, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in Pcyt1a-deficient macrophages, a decreased rate of PC turnover facilitated a shift toward more polyunsaturated FAs in membrane phospholipids, which stemmed their inflammatory potential. (42) Although our study focused on the consequence of exogenous FA treatment on choline transport and subsequent metabolism, we learned that (1) PC metabolism can be regulated because of pathway interruptions and (2) it is possible that alterations in phospholipid FA composition might alter the membrane properties that can affect transport proteins. (43) Finally, many studies have now linked phospholipid biosynthetic pathways with diacylglycerol and triglyceride synthesis, storage, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in these cells, beside UPR or in combination with it, ER stress sensors are mainly activated by changes in the lipid composition and/or saturation of the membranes. It has been recently demonstrated that in adipose-tissue macrophages isolated from obese mice, macrophage-specific depletion of phosphocholine cytidylyltransferase A by limiting the turnover of PC favors the integration of polyunsaturated fatty acid within the ER membrane, therefore reducing ER stress and retaining inflammation [48]. In cancer, tumor-associated macrophages (TAMs) engage the IRE1-dependent ER stress response upon synergistic action of IL-4, IL-6 and IL-10 that promotes cathepsin secretion and increased pro-metastatic phenotype [49].…”
Section: Macrophagesmentioning
confidence: 99%
“…Although Chol does not enter the biosynthesis of other lipid classes, FA can be metabolized into a large range of lipid molecules involved in the metabolic activation of ATM with consequences on AT inflammation and IR ( Figure 2). Membrane composition and optimal membrane properties (i.e., rigidity vs. fluidity) are crucial for a number of cellular processes such as glucose transport [79], immune cell function and inflammatory signaling [11,71,80,81], AT expansion [82] and even insulin signaling [83,84], all of which are compromised during DIO. Membrane dynamics are therefore of particular interest in the study of diabetes-promoting IR and contribute to this "membrane-centric" view of T2D [85].…”
Section: Membrane Dynamics and Inflammatory Signaling In Atmmentioning
confidence: 99%
“…Metabolically activated (MMe) ATMs are part of a rather new concept of an activation profile that was introduced by Kratz et al, and distinguishes them both functionally and phenotypically from the M1 and M2 phenotypes [7,8]. More importantly, MMe ATMs present significant changes in their intrinsic metabolism, including lipid mobilization (i.e., lysosomal catabolism, storage within lipid droplets (LDs) and efflux) and utilization (i.e., free fatty acids (FFA)/Chol synthesis and oxidation for energy production or membrane incorporation) [9][10][11]. On this account, the emerging fields of lipidomics and metabolomics have proven key in the study of ATM function in regard to individual lipid species.…”
Section: Introductionmentioning
confidence: 99%